Investigation into the Effects of Different Restoration Techniques on the Soil Nutrient Status in Degraded Stipa grandis Grassland - Peiqing Zhang; Tianqi Yu; Dan Shan; Ruirui Yan; Lianyun Zhang; Junjie Wang; Qiqige Wuren (Agronomy, 2023)
The degradation and desertification of grassland ecosystems have garnered significant attention both domestically and internationally. Grassland restoration techniques are widely considered a principal measure to promote the sustainable utilization of grasslands, with soil nutrient content being a core indicator for assessing the effectiveness of restoration in degraded grasslands. This study aims to explore the differential impacts of various grassland restoration methods on soil nutrient distribution in degraded Stipa grandis grasslands. Three major restoration methods, i.e., root cutting, enclosure, and fertilization, were applied in the study area. The soil nutrient content was measured and analyzed under the different restoration methods and at varying depths. The results revealed that under all three restoration methods and at different soil depths (0–10 cm, 10–20 cm, 20–30 cm), the organic matter, total nitrogen, total phosphorus, alkali-hydrolyzable nitrogen, alkali-hydrolyzable phosphorus, and available potassium contents were significantly higher than those in the control group (p < 0.05). Furthermore, as soil depth increased, the contents of organic matter and all nutrients gradually decreased. Specifically, regarding the contents of different nutrients, the order of organic matter, total nitrogen, total phosphorus, alkali-hydrolyzable nitrogen, and available phosphorus was as follows: fertilization > enclosure > root cutting > control, while the contents of total potassium and available potassium followed the sequence: fertilization > enclosure > control > root cutting. Additionally, based on the canonical correlation analysis (R2 = 0.88), the total phosphorus content in soil had the greatest impact on soil nutrients, while vegetation cover and plant height contributed the most to vegetation characteristics. In grassland restoration, the increase in soil total phosphorus led to higher vegetation cover and height, mildly influenced plant diversity and density, and simultaneously promoted biomass accumulation. These research findings provide a solid theoretical foundation for the application of grassland restoration techniques, contributing to the sustainable development of grassland ecosystems.